An innovative, simple, fast, and less toxic high-performance liquid chromatographic method for determination of prednisone in capsules - Pedro Henrique Reis da Silva; Paula Cristina Rezende Enéas; Christian Fernandes; Gerson Antônio Pianetti (Universidade de São Paulo, 2017)
ABSTRACT Prednisone is an anti-inflammatory steroid drug widely used in clinical practice. However, no high-performance liquid chromatographic (HPLC) method has been described in the literature for the determination of prednisone in capsules until now. Thus, an HPLC method was developed using a C18 (250x4.0, 5 µm) column, with methanol:water (70:30) as mobile phase at a flow rate of 1 mL/min and detection at 240 nm. The developed method was validated following current Brazilian legislation. Additionally, linearity was assessed by evaluating the assumptions of normality, homoscedasticity, and independency of residuals, and the fit to the linear model. The method showed linearity (r2>0.99) over the range of 14.0-26.0 µg/mL, selectivity, precision (RSD<2.0%), robustness, and accuracy (average recovery of 100.05%). The chromatographic procedure was applied for assay and uniformity content determination of three different batches of prednisone capsules, showing to be suitable for their quality control.